Classic fairy tales : the VCD that reads with me!. (Magnavision, 2005)
3 great stories such as Sleeping beauty, Old mother hubbard, the three little kittens
Volume 3: appropriate to ages two and above
Keywords: Sleeping beauty; Old mother hubbard; Three little kittens